Impact of Peer Support on Acute Care Visits and Hospitalizations for Individuals With Diabetes and Depressive Symptoms: A Cluster-Randomized Controlled Trial - Cherrington, Andrea L. (Diabetes Care, 2018)
OBJECTIVE: Comorbid depression is associated with increased health care utilization and cost. We examined the effects of peer support on acute care (AC) and hospital utilization in individuals with diabetes with or without depressive symptoms. RESEARCH DESIGN AND METHODS: This was a cluster-randomized controlled trial conducted in 2010–2012, with the clusters being practices and their surrounding communities. Adults with type 2 diabetes who wanted help with self-management were eligible to participate. Those without a doctor, with limited life expectancy, with plans to move within the next year, and with an unwillingness to work with a peer advisor were excluded. Intervention participants received 1 year of peer support. Control participants received usual care. The Patient Health Questionnaire (PHQ-8) (range 0–24; 5 indicates mild and 10 indicates moderate depressive symptoms) assessed depressive symptoms. AC and hospital utilization were measured by self-report. Data were collected at baseline, 6 months, and 12 months. Quasi-Poisson regression using generalized estimating equations examined differences in utilization per year attributable to the intervention for those with and without mild depressive symptoms (and separately, moderate depressive symptoms), controlling for imbalance across treatment arms. RESULTS: At baseline, half of the sample reported mild depressive symptoms (52% intervention and 48% control, P = 0.37), a quarter reported moderate depressive symptoms (25% intervention and 26% control, P = 1.0), and there were no significant differences in utilization. A total of 168 intervention (six clusters) and 187 control (five clusters) participants had follow-up data. In individuals with mild depressive symptoms, the incident rate ratio (IRR) for hospitalization among intervention compared with control was 0.26 (95% CI 0.08–0.84) per 10 patient-years. The IRR for AC was 0.55 (95% CI 0.28–1.07) per 10 person-years. Findings were similar for individuals with moderate depressive symptoms. CONCLUSIONS: Peer support lowered AC visits and hospitalizations for individuals with depressive symptoms but not for those without depressive symptoms; these findings can guide resource allocation for population health management.